Sustaining Digital Language Resources and Sign Language - Wallang, Melissa G. (Indian Journal of Educational Technology, 2020)
This paper discusses the need of a multi-modal and multilingual sign language resource by providing insights from the experiences based on the development of digital based sign language resources which are the North East Sign Languages SignBank (A variety of the Indian Sign Language) in a web-based format and the Meghalaya SignBank (A variety of the ISL), a mobile application. It raises the challenges and concerns of sustaining such language resource and its use, drawing upon the cross modal perspectives of archiving human languages, issues in education and the cultural and linguistic diversity of the deaf community in India and particularly the North East region.